A comprehensive review on performance assessment of solar cavity receiver with parabolic dish collector. Issue 2 (15th June 2022) - Maurya, Akanksha; Kumar, Anoop; Sharma, Deepak
ABSTRACT: Cavity receiver integrated with parabolic dish collector is an essential component of the solar thermal energy conversion process for high-temperature applications, such as power generations, process heat demand, and industrial applications. This paper is focused on a comprehensive review and representation of research on solar cavity receiver. The majority of research concentrated on the highest thermal efficiency with the least amount of heat loss and their interactions with solar cavity receiver geometries. The review consists of various combinations of the receiver's geometries along with different heat transfer fluids, and it also give suggestions to improve the performance of the system based on optimized geometrical and operational parameters. The existing literature primarily focused on the experimental and numerical procedures used with different technologies to improve the efficiency of the solar power system. The decrements in heat losses experienced during the conversion of solar energy into thermal energy is used to determine the efficiency of parabolic dish collector systems. The evaluation of convection and radiation losses is essential to improve the thermal performance of the solar power system. Heat loss models and correlations have been discussed to understand the heat loss mechanism for cavity receiver. The present study analyzes a wide range of parameters that affect cavity receiver performance, including aspect ratio, concentration ratio, optimum receiver length, receiver aperture, tilt angle, and inclination angle. The benefits of air curtains, receiver coatings, and other heat transfer enhancement techniques are also briefly reviewed and expected to be useful in modeling and design of cavity receiver with parabolic dish collector system to improve overall performance. One of the most significant aspects of this article is that it covers a wide range of cavity literature encountered in other engineering systems, power generation, and a wide range of other industrial and domestic applications. The cylindrical cavity receiver has shown an average thermal efficiency of 63.9 % using nano-fluid and 56.44 % for pure thermal oil. The hemispherical cavity receiver has shown the daily mean thermal efficiency of 82.66 % using novel soybean oil-based MXene nanofluid. Under the constant parameters, and solar irradiation intensity 300 to 1100 W / m 2, the receiver thermal efficiency varies from 80% to 90%. In case of conical cavity receiver, the maximum thermal efficiency achieved with thermal oil is 78.7%.